1998
DOI: 10.1046/j.1365-2141.1998.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal observation and outcome of nonfamilial childhood haemophagocytic syndrome receiving etoposide‐containing regimens

Abstract: Summary. The long-term outcome of 22 children treated with etoposide-containing regimens for haemophagocytic syndrome (HS) were longitudinally studied; none of them had a family history of the disease. All patients received etoposide-containing (150 mg/m 2 /d) regimens, combined, in 16 cases, with intravenous immunoglobulin (IVIG) and prednisolone. Complete remission (CR) was achieved in 12 patients, partial remission in seven, and early mortality occurred in three. Of the 12 CR patients, only four remain aliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…It is well known that EBV also displays latency II in EBV-associated T-cell lymphomas (Cohen 2000;Forte and Luftig 2011). EBV-HLH is likely to relapse or progress to T-cell lymphoma over months to years (Su et al 1993;Yao et al 1994;Chen et al 1998). The same latency type may be related to the mechanism of disease progression from EBV-HLH to T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that EBV also displays latency II in EBV-associated T-cell lymphomas (Cohen 2000;Forte and Luftig 2011). EBV-HLH is likely to relapse or progress to T-cell lymphoma over months to years (Su et al 1993;Yao et al 1994;Chen et al 1998). The same latency type may be related to the mechanism of disease progression from EBV-HLH to T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients responded to the therapy using a protocol of intravenous immunoglobulin (IVIG)/VP-16, 38 2 had chronic active diseases, and 2 had rapidly progressive diseases.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 Tissues or freshly frozen cells were available for DNA and RNA extraction in 7 cases, including lymph nodes in 2 cases, spleen in 1 case, skin in 1 case, and bone marrow in 3 cases. As controls, 10 specimens of reactive lymphoid hyperplasia (5 cases), IM (2 cases), and nasal type NK/T-cell lymphoma (3 cases) were included.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…7,29,30 These findings suggested to us that the EBV-infected T cells may survive or even proliferate in the cytokine milieu of HPS, in which TNF-␣ is presumed to be the culprit cytokine. 8 Consistent with previous studies, 26 we demonstrated here that EBV LMP-1 could up-regulate TNF-␣ via a TRAFs/NF-B pathway in EBV-infected T cells.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although current therapy has been successfully used to control HPS in patients, 27,28 a substantial percentage of patients who received initial treatment may develop relapsing disease or even progress to T-cell lymphoma. 29,30 Therefore, it is reasonable to speculate whether EBV-infected T cells are less sensitive to the cytokinemediated cytotoxicity than the surrounding uninfected or bystander cells and hence survive or proliferate in the cytokine milieu of HPS. In this study, we performed a series of experiments to test this hypothesis.…”
Section: The Infection Of T Cells By Epstein-barr Virus (Ebv) May Resmentioning
confidence: 99%